Management of copper for crop production - Moreira, Adônis; Moraes, Larissa A.C.; de Melo, Thadeu Rodrigues; Heinrichs, Reges [UNESP]; Moretti, Luiz G. [UNESP] (Elsevier, 2022)
Copper (Cu) is an essential micronutrient for plant growth and development, and its deficiency in plants has been reported in many crop regions. About 50% of agricultural soils have low amounts of Cu available to plants, which impairs the yield and the nutritional quality of crops and derivatives. Under these conditions, both plant Cu uptake and Cu use efficiency (CuUE) are essential for food crop production, since they are complex because all the steps, including root and foliar uptake, assimilation, translocation, and remobilization, are governed by multiple interacting environmental and genetic factors. Translocation of Cu from the roots to the shoots occurs through the xylem and it is not easily retranslocated by the phloem. In no-till cropping systems, proper plant succession helps maintain good nutrient balance in the soil, increases fertility due to regular incorporation of organic matter (OM), and improves soil aeration and water infiltration, enhancing root penetration. However, an inverse relationship occurs between the Cu content and the increase in the volume of soil organic matter (SOM). Since the OM is characterized by containing natural chelating agents, as it accumulates in the soil, forming very stable Cu chelates with fulvic and humic acids, the nutrient availability decreases for the plants. Additionally, the increase in pH caused by the continuous use of limestone also decreases the content of available Cu in some soils, with those located in the tropics. This chapter aims to critically review the factors affecting Cu availability in the soil, its uptake, deficiency, sufficiency, and toxicity levels, and CuUE in crops.
Keywords: Bioavailability; Cu-extractants; Cu-use efficiency; Metabolism in the plant; Uptake mechanism